Influence of karate training lessons on functional parameters of the heart in first-year students - Skorosov K.K. ,; Dorontsev A.V. ,; Medvedev I.N. ,; Razzhivin O.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to monitor the impact of regular karate training on the heart characteristics of first-year students. Methods and structure of the study. 15 male first-year students who had experience in karate training for at least six months 3 times a week were examined. The comparison group consisted of 16 clinically healthy, physically untrained first-year boys. Ultrasound diagnostics of the heart condition were carried out. The Student's t-test value was calculated. Results and conclusions. Those who began to practice karate had a tendency to develop hypertrophy of the left ventricular myocardium, which consisted in an increase in its mass and the development of its walls. The external size of the left ventricle and the volume of its cavity in karatekas remained normal. In addition, they showed a slightly higher rate of myocardial relaxation than in the comparison group. It is clear that karate training for six months strengthens the myocardium of the left ventricle, maintaining the optimum of its internal volume, external dimensions and functionality.